1998
DOI: 10.1099/00221287-144-2-325
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus suis serotype 2 mutants deficient in capsular expression

Abstract: Streptococcus suis serotype 2 is responsible for a wide variety of porcine infections. In addition, it is considered a zoonotic agent. Knowledge about the virulence factors for this bacterium is limited but its polysaccharide capsule is thought to be one of the most important. Transposon mutagenesis with the self-conjugative transposon Tn916 was used to obtain acapsular mutants from the virulent 5. suis type 2 reference strain 5735. Clones were screened by colony-dot ELISA with a monoclonal antibody specific f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
143
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(153 citation statements)
references
References 46 publications
9
143
0
Order By: Relevance
“…Compared with the parent strains, the isogenic unencapsulated mutants of S. suis serotype 2 were more susceptible to phagocytosis by both macrophages and neutrophils (Benga et al, 2008;Chabot-Roy et al, 2006;Charland et al, 1998;Smith et al, 1999a). Moreover, capsule loss reduced the virulence of S. suis in both mouse and swine models of infection (Charland et al, 1998;Smith et al, 1999a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the parent strains, the isogenic unencapsulated mutants of S. suis serotype 2 were more susceptible to phagocytosis by both macrophages and neutrophils (Benga et al, 2008;Chabot-Roy et al, 2006;Charland et al, 1998;Smith et al, 1999a). Moreover, capsule loss reduced the virulence of S. suis in both mouse and swine models of infection (Charland et al, 1998;Smith et al, 1999a).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the parent strains, the isogenic unencapsulated mutants of S. suis serotype 2 were more susceptible to phagocytosis by both macrophages and neutrophils (Benga et al, 2008;Chabot-Roy et al, 2006;Charland et al, 1998;Smith et al, 1999a). Moreover, capsule loss reduced the virulence of S. suis in both mouse and swine models of infection (Charland et al, 1998;Smith et al, 1999a). In contrast, Salasia et al (1995) and Benga et al (2004Benga et al ( , 2005 reported that isogenic unencapsulated mutants showed increased adherence to various types of cells, including porcine endothelial cells and human epithelial cells, when compared with the parent serotype 2 strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once in the bloodstream, S. suis resists phagocytosis and killing by neutrophils and monocytes (Chabot-Roy et al, 2006;Charland et al, 1998;Segura et al, 1998;Smith et al, 1999). In the event that S. suis fails to cause acute fatal septicaemia, bacteria are able to reach the CNS via different mechanisms that are only partially elucidated, such as adhesion to, with or without toxicity, and invasion of brain microvascular endothelial cells (BMEC) (Benga et al, 2005;Charland et al, 2000;Vanier et al, 2004) and/or choroid plexus epithelial cells (Tenenbaum et al, 2005(Tenenbaum et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…The production of this S. suis haemolysin was evidenced in strains collected from diseased pigs, but its role has not been determined [19,27]. Moreover, other surface components may be implicated in the virulence of S. suis [4,11,20].…”
Section: Introductionmentioning
confidence: 99%